Changes in upper and lower body muscle involvement at increasing double poling velocities: an ecological study - Zoppirolli, C.; Pellegrini, B.; Modena, R.; Savoldelli, A.; Bortolan, L.; Schena, F. (Scandinavian Journal of Medicine & Science in Sports, 2017)
This study evaluated muscle activity changes in different body compartments during on-snow double poling at increasing velocities. 21 well-trained, male cross-country skiers performed five 3-min double poling trials on a snowy track at 15, 16.5, 18, 19.5, and 21 km/h (set by an audio-pace system). A sixth trial was performed by maintaining a constant maximal speed. Actual skiing velocities were verified using a photocell system. Only 11 subjects met the pre-defined inclusion criteria during the trials and were included in the data analysis. Electromyographical signals from seven muscles, wrist acceleration and heart rate during the last minute of each trial were recorded. Cycle and poling times were measured from acceleration signals; mean muscular activation over a cycle was calculated for each muscle. With increasing double poling velocities from aerobic to maximal intensity (from 65% to 100% of maximal heart rate), upper limb muscles activation was maintained constant (P > 0.05), while trunk and lower limb involvement increased significantly (P < 0.01) with a linear trend. Rectus abdominis and rectus femoris muscles showed the higher rate of change. Trunk and lower limbs provide a progressively greater contribution to the propulsion when increasing double poling velocities are performed, to support the limited capacity of exercise response of upper body muscles. The remarkable rate of involvement of the muscles near the core region of the body becomes strategic to cope with the increased demands of propulsive power.